Physico-chemical mechanisms involved in the acceleration of the hydration of calcium sulfoaluminate cement by lithium ions. (June 2017) - Cau Dit Coumes, Céline; Dhoury, Mélanie; Champenois, Jean-Baptiste; Mercier, Cyrille; Damidot, Denis
Abstract: This work investigates the influence of lithium ions on the hydration at 25 °C of two calcium sulfoaluminate (CSA) cements comprising 0 or 10% gypsum. Small concentrations of lithium salts (LiOH, LiNO3 ) accelerate the early hydration of both CSA cements either in paste or in diluted and stirred suspension. The effect of the lithium cation is much stronger than its counter-ion. Hydration is accelerated by an increase in the lithium concentration up to 30 μmol Li/g of the used CSA cement (with a high ye'elimite content), and then levels off. The postulated mechanism relies on a fast precipitation of amorphous Li-containing Al(OH)3, which acts as seeds for accelerating the precipitation of amorphous Al(OH)3 that speeds up the whole hydration process. This process seems to be closely related to the one involved in the acceleration of the hydration of calcium aluminate cement by lithium ions.